A game of gods eaudiobook - St. Clair, Scarlett (Hades & Persephone, 2023)
Told in multiple POVs, A Game of Gods is the final installment in the Hades Saga by USA Today bestselling author Scarlett St. Clair. Hades, God of the Dead, has finally made Persephone his in every way possible. With their wedding on the horizon, the couple should be ecstatic. But Demeter is wreaking havoc on their bliss by battering the whole of New Greece with erratic and dangerous weather. At the same time, Theseus continues with his agenda against the Gods, allying with the hate-group Triad in an effort to bring down all of Olympus. Hades refuses to allow anything to stop him from securing Persephone as his bride, but he must play a deep strategic game with the Gods of Olympus to safeguard their future. And it is not entirely clear which Gods are truly on his side. Contains mature themes.